Structural finite element model updating considering soil-structure interaction using ls-dyna in loop - Gun Park; Jongwon Jung; Hyungchul Yoon (Scientific Reports, 2023)
Abstract In this study, a finite element model updating method which can consider soil-structure interaction was developed to analyze the effect of soil properties on the structural response while considering interaction between the soil and the structure. Additionally, LS-DYNA, a commercial finite element program, was included in the loop of the proposed technique using MATLAB to conveniently utilize the complex structures updated by the model. To validate the performance of the proposed method, a large-scale shake table test was conducted. The objective of the validation test was to seek how accurately the proposed model updating method can detect the change in the stiffness. To compare the result of the proposed method with the conventional method, the model updating procedure was conducted with and without considering soil-structure interaction. The proposed finite element model updating method which considers the soil-structure interaction estimated the stiffness of the structure with maximum accuracy of 91%, while the conventional finite element model updating without considering the soil-structure interaction showed maximum accuracy of 88%. By comparing the proposed method with the conventional method without considering the soil-structure interaction, it was confirmed that the proposed method had an 3% higher accuracy on average.